Influence of tobacco smoking and alcohol drinking on dysmenorrhoea: a cross-sectional analysis of data from the Taiwan Biobank - Cheng-Shing Kuo; Kuang-Te Wang; Jerry Cheng-Yen Lai; Shaw-Ji Chen (BMJ Open)
Objectives Dysmenorrhoea, characterised by severe menstrual cramps, affects between 50% and 90% of women of reproductive age and considerably lowers their quality of life.Design Cross-sectional study.Setting This study explored the influence of tobacco smoking and alcohol consumption on dysmenorrhoea, using data from the Taiwan Biobank.Participants Our analysis involved 8567 individuals and examined the associations between dysmenorrhoea and variables such as alcohol consumption, tobacco smoking, demographic characteristics and lifestyle behaviours through multivariable logistic regression.Results The findings reveal a significant association between concurrent alcohol and tobacco use and increased dysmenorrhoea risk, with adjusted ORs suggesting higher risk levels for dual users compared with those who only smoke or drink (adjusted OR (95% CI) both alcohol and tobacco: 3.19 (1.51 to 6.72); only tobacco: 1.21 (0.89 to 1.63); only alcohol: 1.06 (0.53 to 2.13)). Additionally, factors such as higher education level and early menarche were associated with increased dysmenorrhoea risk, whereas regular exercise and multiparity exerted a protective effect against the condition (adjusted OR (95% CI) higher education: 1.43 (1.19 to 1.71); early menarche: 1.37 (1.14 to 1.64); regular exercise: 0.77 (0.64 to 0.93); multiparity: 0.64 (0.52 to 0.77)).Conclusions Our study also highlights the complex interactions between lifestyle factors and dysmenorrhoea, underscoring the need for targeted interventions and lifestyle modifications to mitigate the condition’s effects. Future research should employ longitudinal designs for causal inference and to explore the mechanisms underlying the associations observed in this study.